World Development Report 2005 : A Better Investment Climate for Everyone - World Bank (World Development Report, 2004)
Firms and entrepreneurs of all types-from microenterprises to multinationals-play a central role in growth and poverty reduction. Their investment decisions drive job creation, the availability and affordability of goods and services for consumers, and the tax revenues governments can draw on to fund health, education, and other services. Their contribution depends largely on the way governments shape the investment climate in each location-through the protection of property rights, regulation and taxation, strategies for providing infrastructure, interventions in finance and labor markets, and broader governance features such as corruption. The World Development Report 2005 argues that improving the investment climates of their societies should be a top priority for governments. Drawing on surveys of nearly 30,000 firms in 53 developing countries, country case studies, and other new research, the Report explores questions such as: What are the key features of a good investment climate, and how do they influence growth and poverty? What can governments do to improve their investment climates, and how can they go about tackling such a broad agenda? What has been learned about good practice in each of the main areas of the investment climate? What role might selective interventions and international arrangements play in improving the investment climate? What can the international community do to help developing countries improve the investment climates of their societies? In addition to detailed chapters exploring these and related issues, the Report contains selected data from the World Bank's new program of Investment Climate Surveys, the Bank's Doing Business Project, and World Development Indicators 2004-an appendix of economic and social data for over 200 countries. This Report offers practical insights for policymakers, executives, scholars, and all those with an interest in economic development.